PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA SWALAYAN SINAR BONE WIWIRANO KONAWE UTARA - Titin Anita Lestari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2021)
Given the number of supermarkets (supermarket) which is located in the same area, then by itself would give birth to the fierce competition to seize visitors and buyers. Additionally the competition also came from some retailers in traditional markets and shops are scattered in the same area. Sinar Bone Supermarkets is one of the famous retail among some retail in the city of wiwirano Konawe utara. In the motion of daily operations, Sinar Bone Supermarkets as shopping centers provide a variety of different goods with different types, brands and sizes at varying price levels. Problem formulation, Based on the background outlined above, then the problem is: What is the quality of services that includes Tangible, Realibility, Responsiveness, Assurance, and Empathy effect on customer satisfaction in the Sinar Bone Supermarket wiwirano -konawe Utara .Objective, while the objectives of this research is to determine how much the quality of the services provided by Sinar Bone Supermarket.